Trends in complications after functional endoscopic sinus surgery in Japan: A comparison with a previous study (2007–2013vs. 2013–2017). Issue 5 (October 2020) - Koizumi, Megumi; Suzuki, Sayaka; Matsui, Hiroki; Fushimi, Kiyohide; Yamasoba, Tatsuya; Yasunaga, Hideo
Abstract: Objective: Functional endoscopic sinus surgery (FESS) for chronic rhinosinusitis is considered safe and is widely performed. Techniques and devices for this type of surgery have recently been updated. The purpose of this study was to describe the proportions of complications after FESS (2013–2017) and to compare the results with those from our previous study (2007–2013). Methods: We obtained data on 70, 288 patients who underwent FESS from April 2013 to March 2017 from a Japanese national inpatient database. We classified FESS into four types: single sinus surgery (ESS Type 2), multiple sinus surgery (ESS Type 3), whole sinus surgery (ESS Type 4), and extensive sinus surgery (ESS Type 5). We investigated the proportions of complications after FESS, including cerebrospinal fluid leakage, meningitis, orbital injury, severe hemorrhage, and toxic shock syndrome. We performed a multivariable logistic regression analysis with adjustment for within-hospital clustering to evaluate the association between the occurrence of overall complications and patient characteristics. Results: The proportion of overall complications was 0.50%. The proportions of patients with cranial complications, orbital complications, hemostasis operations, blood transfusion, and toxic shock syndrome were 0.11%, 0.04%, 0.05%, 0.30%, and 0.03%, respectively. The extent of FESS was not associated with the occurrence of overall complications. The occurrence of overall complications was associated with the severity of comorbidities and the academic hospital status. Asthma and use of a microdebrider were associated with a lower occurrence of overall complications. Conclusion: The proportion of overall complications after FESS in the present study was similar to that reported in our previous study. The extent of FESS and eosinophilic chronic rhinosinusitis were not associated with the occurrence of overall complications.